PENGARUH LIKUIDITAS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Syahputri, Ananda Mutiara; Desi Ika; Yani Suryani (Journal Accounting International Mount Hope, 2025)
This study aims to determine the effect of Liquidity and Institutional Ownership on Firm Value with Dividend Policy as a moderating variable. This type of research is a quantitative research. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The sampling technique used the purposive sampling method with a sample of 40 companies. The data analysis technique for this study uses Moderated Regression Analysis (MRA). The results of this study indicate that liquidity and institutional ownership have an effect on firm value. Dividend policy is unable to moderate the effect of liquidity on firm value, while dividend policy is able to moderate the effect of institutional ownership on firm value.